Evaluating mangroves as nature-based solutions for coastal protection under current and future sea level rise scenarios - Jayson-Quashigah, Philip-Neri; Staneva, Joanna; Chen, Wei; Djath, Bughsin’; Mahu, Edem; Appeaning Addo, Kwasi (Frontiers in Marine Science, 2025)
Coastal hazards, such as erosion and flooding, pose significant threats to many coastal areas, and in extreme cases, have led to the decimation of some coastal communities. Historically, management has mostly focused on the use of grey infrastructure such as seawalls and groynes. However, these interventions are costly and can cause unintended consequences, promoting a shift toward Nature-based Solutions (NbS), such as the use of mangroves. Mangroves, particularly, have been proven to protect shorelines due to their ability to attenuate waves and trap sediment. However, there is limited research, particularly in data-deficient regions such as Ghana, West Africa, to support such NbS initiatives. This study explored the potential of mangroves as NbS to mitigate coastal erosion, using the 1D morphodynamic model XBeach. The baseline model was validated against measured coastal profiles, and the results show accurate predictions of sediment volume changes with an overall RMSE of 0.75 m. Based on the calibrations, we explored the effects of mature mangroves at varying densities on the berm and within the intertidal zone under current and projected sea level conditions, on coastal erosion. The results show a significant reduction in sediment volume erosion from 28 m3 to 0.9 m3 in the current situation, representing 97% protection; and from 468 m3 to 2.6 m3 under future sea level rise of 0.233 m by 2040, indicating 99% protection. Notably, high densities of mangroves, introduced on the berm, which is more practical for the area, provided up to 53% reduction in erosion for the current situation and 97% for the future. These scenario-based simulations demonstrate the potential of mangroves as a dynamic coastal defense strategy, with the approach providing a valuable tool for testing and optimizing NbS interventions.